Linking genetic and phenotypic bedaquiline resistance in Mycobacterium tuberculosis strains from Georgia - Nino Maghradze; Chloé Loiseau; Galo Adrian Goig; Nino Bablishvili; Levan Jugheli; Sonia Borrell; Nestani Tukvadze; Russell Ryan Kempker; Zaza Avaliani; Sebastien Gagneux (PLoS ONE, 2025)
Introduction Resistance to bedaquiline – a novel, promising medication against tuberculosis (TB), is already emerging, and uncertainties regarding the role of the different resistance-conferring mutations complicate the development of molecular diagnostic tools for detecting resistance. Mutations in the three genes atpE, pepQ, and Rv0678 have been associated with increased minimum inhibitory concentrations (MICs) to bedaquiline in Mycobacterium tuberculosis (Mtb). Here, we studied the effect of known and novel mutations in these genes on the phenotypic susceptibility to bedaquiline in Mtb isolates from patients with drug-resistant TB in the country of Georgia. Methods We used retrospective Mtb isolates (2011–2019) with whole-genome sequencing data, and prospectively collected diagnostic isolates with phenotypic resistance (2019–2022) to bedaquiline at the Georgian National Reference Laboratory. We determined bedaquiline MIC values using the SensititreTM MYCOTB MIC plate. MIC of 0.12 μg/mL was defined as borderline and MIC ≥ 0.25 μg/mL as a resistant isolate. A phylogeny was inferred to assess the likely role of the identified variants in bedaquiline resistance, while taking into consideration population structure of the strains analyzed. Results We analyzed a total of 69 Mtb isolates and identified 61 mutations across the three target genes. Seventeen (27.8%) of these variants were associated with borderline (0.12 μg/mL) or resistant (≥0.25 μg/mL) MICs to bedaquiline. In addition to six previously described bedaquiline resistance-conferring mutations in atpE and Rv0678, we identified two novel variants in Rv0678 (Leu95Ser and Ile108fs) likely involved in bedaquiline resistance. We found a Tyr92Cys mutation in Rv0678 in two epidemiologically linked isolates, which likely emerged as a consequence of previous exposure to clofazimine. Conclusion Consistent with previous reports, our study confirms that mutations in Rv0678 are the most frequent cause of bedaquiline resistance in Georgia, in addition to an increasing clinical relevance of mutations in atpE, while the role of pepQ mutations remains to be defined.